A socioeconomic analysis of Greek entrepreneurs’ migration to Bulgaria before and after the 2007 crisis - Kapitsinis, Nikos (The Greek Review of Social Research, 2019)
This paper presents a socioeconomic analysis of small and medium-sized entrepreneurs’ migration, based on the differentiation of the social, economic, and institutional conditions. It examines the relocation of small and medium-sized companies from Greece to Bulgaria, comparing the socioeconomic frameworks in the two countries before and after the 2007 global economic crisis. The author adopts the conceptual framework of variegated capitalism, in order to interpret distinct political economies, analysing business decisions for relocation. The analysis draws upon original data collected from a fieldwork conducted in Bulgaria in 2014.